Evaluation of the Toxoplasma gondii IgG Avidity request and results in a tertiary care hospital. Issue 2 (2014) - Güngör, Serdar; Gökmen, Ayşegül Aksoy; Uzun, Berrin; Er, Hüseyin Hakan; Pektaş, Bayram; Kilimcioğlu, Ali Ahmet
No abstract available